2020
DOI: 10.3390/ijms21186661
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF Mass Spectrometry Revealed Significant Lipid Variations in Follicular Fluid and Somatic Follicular Cells but Not in Enclosed Oocytes between the Large Dominant and Small Subordinate Follicles in Bovine Ovary

Abstract: Lipid metabolism in ovarian follicular cells supports the preparation of an enclosed oocyte to ovulation. We aimed to compare lipid composition of a dominant large follicle (LF) and subordinated small follicles (SFs) within the same ovaries. Mass spectrometry imaging displayed the differences in the distribution of several lipid features between the different follicles. Comparison of lipid fingerprints between LF and SF by Matrix Assisted Laser Desorption/Ionisation Time-Of-Flight (MALDI-TOF) mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 84 publications
1
17
0
Order By: Relevance
“…Compared with previous reports, our protocol displays a high degree of robustness, as 26 ion species could be detected on different days. A previously reported lipidomic MALDI-MSI study of fresh-frozen bovine ovary tissue showed a CV <30% based also on three technical replicates, indicating that our protocol allows for the analysis of FFPE tissue with a similar performance to the less complex analysis of fresh-frozen tissue [ 21 ]. In addition, the intraday CV avg (=15 ± 9%) of this study is comparable to intra-section variance CV avg (=16 ± 7%) of 62 lipids obtained by the DESI-MSI of fresh-frozen esophageal adenocarcinoma biopsies [ 22 ].…”
Section: Discussionmentioning
confidence: 83%
“…Compared with previous reports, our protocol displays a high degree of robustness, as 26 ion species could be detected on different days. A previously reported lipidomic MALDI-MSI study of fresh-frozen bovine ovary tissue showed a CV <30% based also on three technical replicates, indicating that our protocol allows for the analysis of FFPE tissue with a similar performance to the less complex analysis of fresh-frozen tissue [ 21 ]. In addition, the intraday CV avg (=15 ± 9%) of this study is comparable to intra-section variance CV avg (=16 ± 7%) of 62 lipids obtained by the DESI-MSI of fresh-frozen esophageal adenocarcinoma biopsies [ 22 ].…”
Section: Discussionmentioning
confidence: 83%
“…Altogether, our label-free SRS images showed that the developing follicles in the 35-day-old flies had lower lipid contents and disrupted lipid distributions compared with the 5-day-old files. Other studies suggest that the development of oocyte depends on the nutritional support from nurse and somatic cells in the earlier stages ( Bogliolo et al, 2013 ; Bertevello et al, 2020 ). Our Raman spectral data also suggest the molecular remodeling toward lipid accumulation happening in the last stages of oogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…A study using a similar MSI approach, but focused on lipid variations, has demonstrated that lipid composition significantly changed during follicle terminal growth in both follicular fluid and somatic cells, especially in granulosa and cumulus cells, with mitigated modulation of lipid composition of the enclosed immature oocyte. Follicular compartment‐dependent turnover and accumulation of specific lipid species, involved in maintenance of plasma membrane integrity, energy storage and signalling, could affect intra‐follicular communication during final follicular growth and might be involved in progress to either follicular atresia or dominance (Bertevello et al., 2020).…”
Section: Discussionmentioning
confidence: 99%